2018
DOI: 10.1038/s41598-018-25706-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Influences on Fetal Growth Vary during Sensitive Periods in Pregnancy

Abstract: Aberrant fetal growth is associated with morbidities and mortality during childhood and adult life. Although genetic and environmental factors are known to influence in utero growth, their relative contributions over pregnancy is unknown. We estimated, across gestation, the genetic heritability, contribution of shared environment, and genetic correlations of fetal growth measures (abdominal circumference (AC), humerus length (HL), femur length (FL), and estimated fetal weight (EFW)) in a prospective cohort of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 67 publications
(73 reference statements)
1
33
0
1
Order By: Relevance
“…It is possible that the locus influences intra-uterine factors during late second trimester and early third trimester, a time period when the growing fetus's demand for oxygen and nutrients is high [13] and the placenta undergoes dramatic transitions to meet these fetal demands [52]. Consistent with these gestational age-dependent findings, we and others have previously found that the effects of fetal genetic variants on fetal growth may be gestation time-specific [53], and the influence of additive genetics on fetal weight increases with gestational age [11][12][13].…”
Section: Plos Geneticssupporting
confidence: 77%
See 1 more Smart Citation
“…It is possible that the locus influences intra-uterine factors during late second trimester and early third trimester, a time period when the growing fetus's demand for oxygen and nutrients is high [13] and the placenta undergoes dramatic transitions to meet these fetal demands [52]. Consistent with these gestational age-dependent findings, we and others have previously found that the effects of fetal genetic variants on fetal growth may be gestation time-specific [53], and the influence of additive genetics on fetal weight increases with gestational age [11][12][13].…”
Section: Plos Geneticssupporting
confidence: 77%
“…Offspring birthweight alone cannot represent the pattern of intrauterine growth at different times during gestation [11]. Previous studies have demonstrated that the genetic contribution to fetal growth, relative to in-utero environmental influences, varies over gestation [11][12][13]. Therefore, different genetic loci may influence fetal growth at different times of gestation, and the same genetic locus may have different effects on fetal growth due to its varied interactions with the in-utero environment by gestation timing [14].…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy is an important "formative period" where a series of interconnected physiological and cellular processes aim to support healthy fetal development [7]. These processes include maternal and paternal genetic factors, hormonal changes, immune system modulation, environmental factors, the microbiome and others [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Intrauterine growth restriction (IUGR) is an adaptation to adverse preconceptual and prenatal conditions such as malnutrition, poor placental supply, genetic disposition, or maternal stress by protecting the development of vital organs (i.e., the brain) while constraining the fetus from reaching its potential size (Gluckman, Hanson, Cooper, & Thornburg, 2008). These unfavorable conditions in utero may affect behavioral functioning and health in later life via prenatal programming during developmental periods of high organ plasticity (Barker, 2007; Gluckman et al, 2008; Workalemahu et al, 2018). IUGR is associated with small for gestational age (SGA) birth, low birth weight (<2,500 g), preterm birth (<37 weeks’ gestational age), and increased long-term morbidity (Raikkonen & Pesonen, 2009).…”
mentioning
confidence: 99%